Experimental and Numerical Analysis of Spun Pile-to-Pile Cap Connection with Reinforced Concrete Infill under Cyclic Loading - Alfetra Henoch Tandita; Yuskar Lase; Widjojo Adi Prakoso; Mulia Orientilize (Rekayasa Sipil, 2022)
Numerical study was conducted by using ABAQUS software to investigate two issues on spun pile connections. The issues are usage of non-shrinkage concrete infill cast inside hollow of pile and ductility. An experimental test was carried out to investigate the effect of two different concrete infill types which were common concrete fc’ 35 MPa and non-shrinkage concrete fc’ 54 MPa. A finite element model was validated against experimental test. The results were compared in terms of hysteresis curve, ductility, and performance level. Ductility is one of the important parameters to describe performance of spun pile connections under seismic load. There are different approaches to calculate ductility and this leads to four different ductility values. Hence, ductility of spun pile with concrete infill is in the range of 3.2 to 4.8. Behavior of spun pile with non-shrinkage concrete infill is slightly improved although the results were almost similar.